Development of resource support institutions for the sectoral implementation of the sustainable development goals: problems and mechanisms - E. Yu. Shatskaya (Вестник Северо-Кавказского федерального университета)
The article, aimed at summarizing the features of the functioning of the institutions of resource provision for the sectoral implementation of the Sustainable Development Goals, presents the main problems of their development, both investment and methodological. To improve the efficiency of the functioning of the institutions under consideration, key measures are proposed. The principles of the formation of key indicators of the effectiveness of the functioning of development institutions in the innovation sphere are determined, the catalysts of socio-economic development of the Russian innovation infrastructure are grouped.